PARADIGMA DISTINGTIF MAQASID SYARI’AH DAN MAQASID AL-QUR’AN - Darmawan, Kasis (Statement: Jurnal Media Informasi Sosial dan Pendidikan, 2024)
The study of maqasid syari’ah and maqasid Al-Qur’an is a crucial discourse in contemporary Islamic legal studies. Although both are rooted in divine revelation, there are fundamental differences in their paradigms, scopes, and approaches. Maqasid syari’ah focuses on the preservation of five essential human needs (dharuriyyat): religion, life, intellect, lineage, and property, with an orientation towards regulating social life. On the other hand, maqasid Al-Qur’an encompasses a broader scope, reflecting the universal objectives of the Qur'an, such as justice, compassion, and cosmological balance. This study aims to explore the distinctions between these two paradigms. A qualitative approach is employed through a literature review of classical and modern works discussing these concepts. The findings indicate that maqasid Al-Qur’an offers a more holistic framework for understanding the Qur'an's message across various dimensions of life, while maqasid syari’ah tends to provide practical guidance within legal and social contexts. This research makes a significant contribution to the development of Islamic studies by offering an integrative and relevant perspective to address modern global challenges. The findings are expected to serve as a foundation for formulating Islamic-based solutions oriented toward universal values and the overall welfare of humanity.